"Concern for community": Case of cooperatives in the Cordillera region, Philippines. Issue 1 (June 2021) - Launio, Cheryll C.; Sotelo, Mary Cris B.
Highlights: Cooperatives have high compliance in allocating community development funds. There is a relatively low actual utilization rate, especially among small cooperatives. Cooperatives' community projects are mostly solicited donations for education, health, and environment services. Perceived barriers to CDF use are lack of funds, lack of concrete CDF-use plan, lack of member-participation, and poor coordination with partners. Intentional CDF use, capability building on project planning and management, active monitoring of development plans by CDA are recommended. Abstract: One area where cooperatives supposedly differ from corporate capitalism is their higher level of concern for the community beyond its membership base. ICA seventh principle is thus "concern for community." Philippine cooperative law mandates cooperatives to allot at least three percent of their yearly net surplus for community development funds (CDF). This study presents how cooperatives build and use their CDF and determine their constraints in conducting community projects. It used data from a mailed survey and annual performance reports. Findings indicate high compliance in allocating for CDF but a relatively low actual utilization rate, especially among small cooperatives. Actual CDF spending is highly positively associated with total assets, net surplus, cooperative size, and the total number of cooperative members. Common projects implemented are mostly in the area of education, health, and the environment. Perceived challenges in implementing community development projects include limited funds, lack of member-participation, poor coordination with partner organizations, and lack of a concrete plan for using CDF. The study recommends strengthened support for cooperatives to plan for intentional CDF use through capacity building on project planning and management, more functional monitoring and evaluation of development plans, and social audit reports, and further impact research.